2022
DOI: 10.3389/fnut.2022.886902
|View full text |Cite
|
Sign up to set email alerts
|

The Therapeutic Effect of SCFA-Mediated Regulation of the Intestinal Environment on Obesity

Abstract: Intestinal environment disorder is a potential pathological mechanism of obesity. There is increasing evidence that disorders in the homeostasis of the intestinal environment can affect various metabolic organs, such as fat and liver, and lead to metabolic diseases. However, there are few therapeutic approaches for obesity targeting the intestinal environment. In this review, on the one hand, we discuss how intestinal microbial metabolites SCFA regulate intestinal function to improve obesity and the possible m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 144 publications
(107 reference statements)
0
17
0
Order By: Relevance
“…SCFAs have been proved to stimulate energy consumption by promoting lipid oxidation, and the increase in SCFAs production can stimulate a large number of hormones and neural signals in different organs and tissue sites, thereby cumulatively inhibiting short-term appetite and energy intake ( 48 , 49 ). In addition, SCFAs can also prevent diet-induced obesity by inhibiting the activity of Histone Deacetylase 3 in intestinal epithelial cells ( 15 ). Studies have shown that unclassified Muribacullaceae ( 50 ), unclassified lachnospiraceae ( 51 ), and Alloprevotella ( 52 ) are all intestinal SCFAs-producing bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…SCFAs have been proved to stimulate energy consumption by promoting lipid oxidation, and the increase in SCFAs production can stimulate a large number of hormones and neural signals in different organs and tissue sites, thereby cumulatively inhibiting short-term appetite and energy intake ( 48 , 49 ). In addition, SCFAs can also prevent diet-induced obesity by inhibiting the activity of Histone Deacetylase 3 in intestinal epithelial cells ( 15 ). Studies have shown that unclassified Muribacullaceae ( 50 ), unclassified lachnospiraceae ( 51 ), and Alloprevotella ( 52 ) are all intestinal SCFAs-producing bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the family Erysipelotrichaceae enriched after 2 weeks in the sham control group may contribute to gut inflammation and may serve as a potential microbial target for addressing metabolic disorders including T2DM ( 39 , 40 ). Furthermore, the ratio of Firmicutes/Bacteroidetes decreased in the OLED group 1 to 2 weeks after OLED PBM, which may be related to an increase in the secretion of GLP-1 and insulin due to the abundance of gut microbial species that produce short-chain fatty acids ( 46 ). Therefore, the alteration of the gut microbiome observed at 1 to 2 weeks after OLED PBM may be related with dynamic changes of GLP-1 and insulin at 1 and 4 weeks after OLED PBM.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, the use of duodenal or external PBM in small animal models resulted in similarly delayed alterations of the gut microbiome after 1 or 2 weeks of PBM, which supports our results ( 34 , 47 ). Therefore, together with the alteration of the gut microbiome, dynamic fluctuations in serum GLP-1 and insulin, and improved IR as demonstrated by HOMA-IR from 1 week to 4 weeks in the OLED PBM group, duodenal OLED PBM may influence the abundance of the gut microbial species that produce a short-chain fatty acid, resulting in a reduction in serum glucose levels, and IR by increasing GLP-1 and insulin ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…Short-chain fatty acids act as messengers between gut microbes and hosts, directly regulating host metabolic health by engaging in a range of tissue-specific mechanisms related to appetite regulation, energy expenditure, glucose homeostasis, and immune regulation ( 19 , 20 ). However, the interaction between the microbiota and the number and proportion of SCFAs and their role in obesity is very complex ( 21 ).…”
Section: Introductionmentioning
confidence: 99%